以加入WTO为契机加快县域经济发展 ：迁安市发展战略的思考 = WTO accession and counties' economic development : the case of Qian'an City - 张国栋 Zhang, Guodong (2008)
Using Qian’an city of Hebei Province as a case, this thesis first analyzes both positive and negative effects of joining WTO and then discusses the strategies for the development of a country’s economy.